1993
DOI: 10.1007/bf00351853
|View full text |Cite
|
Sign up to set email alerts
|

Heterobasidion annosum 5.8s ribosomal DNA and internal transcribed spacer sequence: rapid identification of European intersterility groups by ribosomal DNA restriction polymorphism

Abstract: Using conserved fungal ribosomal gene sequences the internal transcribed spacer (ITS) regions one and two (ITS1, ITS2) and the 5.8s ribosomal RNA gene (rRNA) of Heterobasidion annosum were amplified by the polymerase chain reaction (PCR). The nucleotide sequence was determined in three European intersterility groups (ISG-S, -F and -P). Three sequence variants of the ITS were found in ISG-S isolates. The sequence of the ITS of ISG-F differed by two residues from the major ISG-S sequence variant. The ISG-P seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
26
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 14 publications
9
26
0
Order By: Relevance
“…We also observed a greater accumulation of iron in P. sylvestris roots in response to exposure to H. annosum s.s. than in response to the other two species . Heterobasidion parviporum and H. abietinum are genetically related to each other more closely than to H. annosum s. s. (Karjalainen 1996;Kasuga et al 1993), which was confirmed by evolutionary studies by Dalman et al (2010). This can explain the similar response of the host to H. parviporum and H. abietinum.…”
Section: Discussionmentioning
confidence: 55%
“…We also observed a greater accumulation of iron in P. sylvestris roots in response to exposure to H. annosum s.s. than in response to the other two species . Heterobasidion parviporum and H. abietinum are genetically related to each other more closely than to H. annosum s. s. (Karjalainen 1996;Kasuga et al 1993), which was confirmed by evolutionary studies by Dalman et al (2010). This can explain the similar response of the host to H. parviporum and H. abietinum.…”
Section: Discussionmentioning
confidence: 55%
“…Thus, no ITS polymorphisms have been observed within the European H. annosum s.s. and H. abietinum, while a relatively low degree of variation has been found within the European H. parviporum and North American S and P intersterility groups (Kasuga et al 1993, Harrington et al 1998), as well as within H. araucariae (Harrington et al 1998) and H. insulare . During study I, the ITS alleles of Chinese H. annosum s.l.…”
Section: Its Rdna Markers (I Ii)mentioning
confidence: 99%
“…species complex was long regarded as a single cosmopolitan species with a wide host range, but mating experiments have revealed the existence of five separate Heterobasidion species showing differences in their host tree preferences (Korhonen 1978a, Chase and Ullrich 1988, Capretti et al 1990, Korhonen et al 1992, Niemelä and Korhonen 1998. Differentiation between these biological species has been confirmed using numerous different molecular approaches including isoenzyme analysis (Karlsson and Stenlid 1991, Otrosina et al 1993, Maijala et al 1995, Goggioli et al 1998), fatty acid and sterol profiles (Müller et al 1995), and various genetic marker molecules (Fabritius and Karjalainen 1993, Kasuga et al 1993, Stenlid et al 1994, La Porta et al 1997, Garbelotto et al 1998, Goggioli et al 1998, Vainio et al 1999, Kasuga and Mitchelson 2000, Johannesson and Stenlid 2003, Maijala et al 2003.…”
Section: Heterobasidion Annosum Species Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative humidity was set at maximum (95%) with an 18 h, 18 °C day and 6 h, (Kasuga et al, 1993).…”
Section: Tree Seedlingsmentioning
confidence: 99%